Identification of CYP2C19*4B: pharmacogenetic implications for drug metabolism including clopidogrel responsiveness - Scott, SA (2011)
CYP2C19 is a principal enzyme involved in the bioactivation of the antiplatelet prodrug clopidogrel and common CYP2C19 loss-of-function alleles are associated with adverse cardiovascular events. To assess the impact of the CYP2C19*17 increased activity allele in the Ashkenazi Jewish (AJ) and Sephardi Jewish (SJ) populations and to determine the frequencies of additional variant alleles, 250 AJ and 135 SJ individuals were genotyped for CYP2C19*2–*10, *12–*17, *22 and P-glycoprotein (ABCB1) c.3435C>T. Importantly, CYP2C19*4, a loss-of-function allele, was identified in linkage disequilibrium with *17. This novel haplotype, designated CYP2C19*4B, significantly alters the interpretation of CYP2C19 genotyping when testing *17. Moreover, genotyping CYP2C19*17 changed the frequency of extensive metabolizers from ~70 to ~40%, reclassifying ~30% as ultrarapid metabolizers. Combining CYP2C19 and ABCB1 identified ~1 in 3 AJ and ~1 in 2 SJ individuals at increased risk for adverse responses to clopidogrel. These data underscore the importance of including *4B and *17 when clinically genotyping CYP2C19.